Endosomal Maturation, Rab7 GTPase and Phosphoinositides in African Swine Fever Virus Entry - Cuesta-Geijo, Miguel A. (Public Library of Science, 2012)
Here we analyzed the dependence of African swine fever virus (ASFV) infection on the integrity of the endosomal pathway. Using confocal immunofluorescence with antibodies against viral capsid proteins, we found colocalization of incoming viral particles with early endosomes (EE) during the first minutes of infection. Conversely, viral capsid protein was not detected in acidic late endosomal compartments, multivesicular bodies (MVBs), late endosomes (LEs) or lysosomes (LY). Using an antibody against a viral inner core protein, we found colocalization of viral cores with late compartments from 30 to 60 minutes postinfection. The absence of capsid protein staining in LEs and LYs suggested that virus desencapsidation would take place at the acid pH of these organelles. In fact, inhibitors of intraluminal acidification of endosomes caused retention of viral capsid staining virions in Rab7 expressing endosomes and more importantly, severely impaired subsequent viral protein production. Endosomal acidification in the first hour after virus entry was essential for successful infection but not thereafter. In addition, altering the balance of phosphoinositides (PIs) which are responsible of the maintenance of the endocytic pathway impaired ASFV infection. Early infection steps were dependent on the production of phosphatidylinositol 3-phosphate (PtdIns3P) which is involved in EE maturation and multivesicular body (MVB) biogenesis and on the interconversion of PtdIns3P to phosphatidylinositol 3, 5-biphosphate (PtdIns(3,5)P(2)). Likewise, GTPase Rab7 activity should remain intact, as well as processes related to LE compartment physiology, which are crucial during early infection. Our data demonstrate that the EE and LE compartments and the integrity of the endosomal maturation pathway orchestrated by Rab proteins and PIs play a central role during early stages of ASFV infection.